Achieving efficiency and effectiveness in Purchasing and Supply Management: Organization design and outsourcing. Issue 4 (October 2017) - Bals, Lydia; Turkulainen, Virpi
Abstract: As a function with a strategic role, Purchasing and Supply Management (PSM) needs to continuously find ways to improve its efficiency and effectiveness. One potential way to specifically addressing efficiency targets is to outsource parts of the purchasing process. While outsourcing remains one of the most prevalent business practices in various areas, many businesses fail to realize the benefits anticipated from their outsourcing initiatives. Research reports that one major reason for these outsourcing challenges lies in the design of the focal organization. In this paper, we take an organization design view to outsourcing in the PSM context. Based on a multi-year case study from 2010 to 2013 at a global chemical and pharmaceutical company, we elaborate how the organizational design of the PSM function relates to outsourcing opportunities in order to increase efficiency and effectiveness by allocating internal resources to more value-adding activities. The case illustrates how an activity-based organizational design of PSM can support outsourcing of some parts of the purchasing process. Highlights: Purchasing and Supply Management (PSM) can use outsourcing to improve efficiency and effectiveness. Organization design of the focal firm can be a challenge to outsourcing. The activity-based organizational design is analyzed in the context of Purchasing and Supply Organization (PSO) outsourcing. The case study illustrates how an activity-based design of the PSO can support outsourcing parts of PSM. This relationship is discussed in light of organizational modularity.